Writing, psychology, production and care: ethics, aesthetics and politics - Silveira Lemos, Flavia Cristina; Nascimento, Maria Livia do; Galindo, Dolores [UNESP] (Univ Fed Rio Janeiro, 2016)
This article intends to discuss the writing on research as meetings and conversations through self care and the others' care practices, with Foucault, Deleuze and Guattari as intercessors. The aim was to analyse notes, letters and writing through the sharing of knowledge and experimentation to friends as a critical intervention of the present. Create, by writing and reading, an analyse producer of freedom in the history of itself thought was, to stoics, pythagoreans and epicureans, a challenge to seek a transformation of self and a displacement of where they were. This is possible preparing a booklet to write thoughts from daily life, where it can be written things to not get lost in an instability of attention, which can constitutes a care stocks.
Keywords: Writing; Letters; Research; Psychology; Care of themselves and of the others